The impact of intensified training with a high or moderate carbohydrate feeding strategy on resting and exercise-induced oxidative stress - Wadley, A. J.; Killer, S. C.; Svendsen, I. S.; Gleeson, M. (European Journal of Applied Physiology, 2015)
PURPOSE: This study investigated the impact of intensified training (IT) and carbohydrate (CHO) supplementation on resting and exercise-induced oxidative stress.